2017
DOI: 10.1520/gtj20160102
|View full text |Cite
|
Sign up to set email alerts
|

1 g Model Tests on the Displacement Accumulation of Large-Diameter Piles Under Cyclic Lateral Loading

Abstract: Large-diameter monopiles are an established foundation type for offshore wind energy converters. A crucial aspect in the design of such piles is the bearing behavior under cyclically acting wind and wave loads, namely the accumulation of deflections and rotations under these loads. Regarding the prediction of the behavior under cyclic one-way load, some empirical approaches and also numerical simulation methods exist. In contrast, the behavior under cyclic two-way loading is widely unclear and must be investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…Nine piles were installed per strongbox, with a minimum center-to-center spacing of 7.4D. This layout was chosen to avoid significant boundary effects while maximizing the number of tests per strongbox sample; the center-to-center spacing is in line with previous studies (e.g., Leblanc et al 2010;Abadie 2015;Albiker et al 2017).…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine piles were installed per strongbox, with a minimum center-to-center spacing of 7.4D. This layout was chosen to avoid significant boundary effects while maximizing the number of tests per strongbox sample; the center-to-center spacing is in line with previous studies (e.g., Leblanc et al 2010;Abadie 2015;Albiker et al 2017).…”
Section: Sample Preparationmentioning
confidence: 99%
“…The power-law coefficient A has been found to vary with ζ b and ζ c (Leblanc et al 2010;Nicolai and Ibsen 2014), and the power-law exponent α has often been reported as a constant within individual studies (Leblanc et al 2010;Nicolai and Ibsen 2014;Albiker et al 2017). However, Truong et al (2019) suggested that α varies with ζ c and D R .…”
Section: Ratcheting Responsementioning
confidence: 99%
See 1 more Smart Citation
“…The subsequent systematic experimental investigations of Rosquoet et al (2007), and Truong & Lehane (2015) show that the accumulation coefficient (α y ) depends primarily on the cyclic load ratio ( c ) and to a lesser extent the cyclic magnitude ratio ( b ), and varies from a negative value for two-way loading ( c = -1) to between about 0.05 and 0.2 at  c values in the range of -0.5 to 0.75 (noting  c = 0 corresponds to one-way loading with H min = 0). LeBlanc et al (2010) and Albiker et al (2017) present formulations based on 1-g small scale tests in which the accumulation coefficient is considered independent of sand relative density, although scale issues associated with the very low stress level prevalent in these tests need to be acknowledged. It is also of note that Albiker et al (2017) observed a dependency of the accumulation coefficient on the lateral load eccentricity as well as a difference between rigid and flexible piles.…”
Section: Introductionmentioning
confidence: 99%
“…LeBlanc et al (2010) and Albiker et al (2017) present formulations based on 1-g small scale tests in which the accumulation coefficient is considered independent of sand relative density, although scale issues associated with the very low stress level prevalent in these tests need to be acknowledged. It is also of note that Albiker et al (2017) observed a dependency of the accumulation coefficient on the lateral load eccentricity as well as a difference between rigid and flexible piles. Cyclic loading applied to monopiles is not uniform and a number of studies have examined the ability of the method of superposition presented by Lin & Liao (1999) to predict pile response under various packages of (uni-directional) cycles.…”
Section: Introductionmentioning
confidence: 99%